The rules of standing of the European Union: a contextual understanding - Bradford, J (2019)
This thesis looks at the context surrounding the EU standing rules for the individual applicant. It seeks to build upon the extensive academic literature on this topic, by further exploring how far this context can explain and justify the approach taken towards the rules themselves, which have generally been considered to be restrictive in character. The analysis is conducted by reference to a selection of factors which represent part of the wider constitutional context.